PENDAMPINGAN LEGALISASI AMAL USAHA MUHAMMADIYAH DI KOTA BATU - Agustin Dwi Haryanti; Muhamad Wildan Affan; Novitasari Agus Saputri (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat, 2020)
Muhammadiyah's Charitable Business is one of the efforts built by the Association to achieve certain goals and objectives. Muhammadiyah's central leadership in charge of various Muhammadiyah business charities in various regions emphasized the legality of each AUM. In AUM found in Batu, there are still many AUMs that do not have legality. Therefore, in order to realize AUM which has legality, the servants take a variety of approaches starting from the presentation of the importance of legality and legality flow and ending with assistance in the process of ownership of legality in the form of SK establishment and NIB.